Direct laser writing of resonant periodic nanostructures in thin light-emitting films of CdSe/CdZnS core/shell nanoplatelets - Azizov, Ruslan (2023)
Core/shell CdSe/CdZnS nanoplatelets (NPLs) are a promising class of nanomaterials for lasing applications owing to their low thresholds and high stability of stimulated emission generation as compared with many other types of colloids. Moreover, they can be self-assembled into high-quality thin films by simple methods of deposition. However, the high throughput and reproducible methods for nanopatterning of such films for advanced light-emitting applications are still missing. In this work, we show direct laser writing on thin films assembled from CdSe/CdZnS NPLs using either spin-coating or the self-assembly method for the purpose of fabricating. Using theoretical calculations, we design the period of the structures to achieve high quality-factor optical modes in the emission band of NPLs. In these nanostructured NPL films, fabricated according to the design, we observe photoluminescence enhancement and directional outcoupling effects. The proposed approach holds great potential for LEDs with improved outcoupling and for distributed feedback lasers or lasers based on bound states in the continuum with directly written optical cavities.